2017
DOI: 10.1038/srep44170
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diurnal distribution of carbohydrates and fat on glycaemic control in humans: a randomized controlled trial

Abstract: Diurnal carbohydrate and fat distribution modulates glycaemic control in rodents. In humans, the optimal timing of both macronutrients and its effects on glycaemic control after prolonged consumption are not studied in detail. In this cross-over trial, 29 non-obese men were randomized to two four-week diets: (1) carbohydrate-rich meals until 13.30 and fat-rich meals between 16.30 and 22.00 (HC/HF) versus (2) inverse sequence of meals (HF/HC). After each trial period two meal tolerance tests were performed, at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 64 publications
2
54
0
4
Order By: Relevance
“…Postprandial increases in glucose differ dramatically between individuals, even to similar foods [11], and are determined not only by the speed and quantity of insulin and glucagon secretion, but also by an array of variables including body composition, age, microbiome, fiber intake, and circadian changes in insulin sensitivity [11][12][13].…”
Section: Gi Is Affected By Many Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Postprandial increases in glucose differ dramatically between individuals, even to similar foods [11], and are determined not only by the speed and quantity of insulin and glucagon secretion, but also by an array of variables including body composition, age, microbiome, fiber intake, and circadian changes in insulin sensitivity [11][12][13].…”
Section: Gi Is Affected By Many Variablesmentioning
confidence: 99%
“…In addition to the speed of digestion and absorption of a specific carbohydrate, the kinetics and quantity of insulin secretion, the inhibition of glucagon release, and gastric emptying directly determine postprandial glucose levels [3,4,7,8,11,12]. Moreover, GI is highly circadian and increases in blood glucose for similar meals are two to three times greater in the evening as compared to the morning [13]. lipogenic and trophic metabolic signals.…”
Section: Box 1 Gi Conceptmentioning
confidence: 99%
“…Epidemiological studies in humans show that increasing carbohydrate intake at breakfast while simultaneously reducing fat intake seems protective against the development of diabetes and metabolic syndrome [9,10]. Similarly, we recently showed that a diet in which fat is mainly eaten in the morning and carbohydrates mainly in the evening (compared with the reverse order) worsens glycaemic control in people with prediabetes [11] and alters substrate oxidation and adipokine secretion [12]. These studies indicate that timing of carbohydrates and fat in an important factor influencing metabolic health.…”
Section: Introductionmentioning
confidence: 88%
“…The study was registered at clinicaltrials.gov as NCT02487576. Details of the study design, the recruitment of participants, inclusion and exclusion criteria, and dietary interventions were published elsewhere [11,12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation